Preface: The World Society Foundation: History and Practice (Decentering European studies: perspectives on Europe from its beyond, 2025)
The aim of this preface is twofold. First, we trace the historical roots of the concept of “world society,” as it pertains to the funding behind this book and the motivation of the World Society Foundation (WSF) to bring together researchers from various parts of the globe to write about Europe from their respective regional perspectives. Because Peter Heintz, the founder of the WSF, was especially influential in shaping the Foundation’s approach to the making of a global society through research funding, we focus on his work. Second, we delve into the Foundation’s funding activities over the last forty years. In this respect, the present volume is well inscribed in the Foundation’s historical mission. Through its first “Writing Lab for Global South Scholars,” of which this book is a result, the World Society Foundation has developed a new funding tool guided by the conviction that such a novel sponsoring pursuit will provide researchers from the Global South (and the Global East) better access not only to resources within the Foundation but also beyond. In support of its core purpose of strengthening research on and from a world society while also promoting a diversity of voices in scholarship, the World Society Foundation brought these different perspectives into a dialogue, in particular through the regular activities of the writing lab. This preface, therefore, serves to situate this edited volume within the historical context of the Foundation’s philosophy and past research funding activity. In line with these past practices, the Foundation has gathered here researchers from different parts of the world and diverse cultural, historical, and academic contexts, who emanate from an array of disciplines and rely on a variety of theoretical and methodological bases to address topics relevant to an understanding of contemporary Europe.